2021
DOI: 10.1108/ejmbe-09-2020-0261
|View full text |Cite
|
Sign up to set email alerts
|

Using the Z-score to analyze the financial soundness of insurance firms

Abstract: PurposeDespite the sophisticated regulatory regime established in Solvency II, analysts should be able to consider other less complex indicators of the soundness of insurers. The Z-score measure, which has traditionally been used as a proxy of individual risk in the banking sector, may be a useful tool when applied in the insurance sector. However, different methods for calculating this indicator have been proposed in the literature. This paper compares six different Z-score approaches to examine which one bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…It allows evaluating default risk across banks with varying aims or ownership. It applies equally to all banks, whether they choose low risk/low return or high risk/high return strategies (Čihák and Hesse, 2010; Moreno et al , 2021). A bank with less capitalization might have a comparable or greater Z-score by having higher risk-adjusted returns.…”
Section: Methodology and Datamentioning
confidence: 99%
“…It allows evaluating default risk across banks with varying aims or ownership. It applies equally to all banks, whether they choose low risk/low return or high risk/high return strategies (Čihák and Hesse, 2010; Moreno et al , 2021). A bank with less capitalization might have a comparable or greater Z-score by having higher risk-adjusted returns.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Moreover, the variables that ensure sound insurance system in US are the firm specific characteristics, including the exposure to natural catastrophes and macroeconomics conditions. Moreno et al (2021) showed that the Z-score of insurance firms can be calculated by ROA and capitalization with the standard deviation of returns, the Z-score index is an early warning for micro-prudential supervision. Additionally, they supported on convincing a clearer picture of insurance firms' risk factors in Spain.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The financial sector also provides a mechanism to assess investment and performance decisions. Managers should develop an RM strategy consistent with the dynamic environment and the firm's risk appetite (Atluntas et al , 2011; Moreno, et al , 2021).…”
Section: The Model and Hypothesis Developmentmentioning
confidence: 99%
“…The financial sector also provides a mechanism to assess investment and performance decisions. Managers should develop an RM strategy consistent with the dynamic environment and the firm's risk appetite (Atluntas et al, 2011;Moreno, et al, 2021). Efficient risk integration is the bottom line of the RM process, where interrelations among risks and risk prioritization are addressed.…”
Section: The Model and Hypothesis Developmentmentioning
confidence: 99%